2007
DOI: 10.1016/j.bbr.2006.07.027
|View full text |Cite
|
Sign up to set email alerts
|

Colony formation of C57BL/6J mice in visible burrow system: Identification of eusocial behaviors in a background strain for genetic animal models of autism

Abstract: Deficits in social interaction are primary characteristics of autism, which has strong genetic components. Genetically-manipulated mouse models may provide a useful research tool to advance the investigation of genes associated with autism. To identify these genes using mouse models, behavioral assays for social relationships in the background strains must be developed. The present study examined colony formation in groups of one male and three female mice (Experiment 1) and, groups of three male mice (Experim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
86
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(90 citation statements)
references
References 64 publications
(81 reference statements)
4
86
0
Order By: Relevance
“…Although the scent marking response to the novel context was not as large as that to a novel mouse, this likely reflects the continued presence of rough paper flooring in the novel context [5,20]. C57 mice are used as a common background strain for knockout mice relevant to disorders such as autism that include deficits in social communication, social motivation, and amicable relationships [1,3,[15][16]51]. The present study demonstrated that C57 as well as CD-1 mice display good social recognition as indexed by scent marking behavior.…”
Section: Discussionmentioning
confidence: 99%
“…Although the scent marking response to the novel context was not as large as that to a novel mouse, this likely reflects the continued presence of rough paper flooring in the novel context [5,20]. C57 mice are used as a common background strain for knockout mice relevant to disorders such as autism that include deficits in social communication, social motivation, and amicable relationships [1,3,[15][16]51]. The present study demonstrated that C57 as well as CD-1 mice display good social recognition as indexed by scent marking behavior.…”
Section: Discussionmentioning
confidence: 99%
“…In nature, individual male mice tend to be solitary, forming their own territories following puberty [3,4]. However, sociality and "amicable" (affiliative) relationships as well as aggression have been documented in male mice in a semi-natural habitat, the visible burrow system (VBS) [5][6][7]. The VBS enclosures provide multiple visible tunnels and burrows in addition to an open "surface" area, to evaluate complicated natural behaviors and social structures among rodents [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…The VBS enclosures provide multiple visible tunnels and burrows in addition to an open "surface" area, to evaluate complicated natural behaviors and social structures among rodents [6,7]. In the VBS, all-male groups of mice of the C57BL/6J (B6) strain, commonly used as a background for genetic manipulations in mice [8][9][10], displayed active (aggressive) interaction during the first few hours of the colony formation followed by a strong tendency to huddle together in a nest chamber during the inactive (light) period as well as during active (dark) periods [5]. The shift from aggressive interaction to amicable huddling accompanied by decreased active social interaction such as approaches, contacts, flight, and chase between male mice occurs over time, as animals habituate to the colony situation and become familiar with colony mates [5].…”
Section: Introductionmentioning
confidence: 99%
“…Studies that have examined social dominance in groups of male laboratory mice have limited their scope to the emergence of an alpha male rather than determining finer details regarding the rank order of all individuals (Ely & Henry, 1978;Lewejohann et al, 2009). Moreover, previous studies of social dominance in the laboratory have limitations such as small group sizes, short duration of observations and few replicated groups (Arakawa, Blanchard, & Blanchard, 2007;Ely & Henry, 1978;Lewejohann et al, 2009;So, Franks, Lim, & Curley, 2015).…”
mentioning
confidence: 97%